Development of a watershed modeling selection program and simple equations as an alternative to complex watershed modeling - Cho, Yongdeok, author; Roesner, Larry A., advisor; Grigg, Neil S., committee member; Arabi, Mazdak, committee member; Stednick, John, committee member (Colorado State University. Libraries, 2013)
Population pressures, land-use conversion and its resulting pollution consequences appear to be the major diffuse pollution problems of today. Research also indicates that the increase in imperviousness of land due to urbanization increases the volume, rate of stormwater runoff causing increased channel erosion and flooding downstream, water quality contamination, aquatic biota, and drinking water supplies. In the past, negative impacts were never seriously considered as urbanization increased, but the attitude of citizens and governments are changing and people now want to retain, restore or rehabilitate existing waterways, and manage future urban and rural development in order to improve environmental conditions. Water quality management in the contributing watersheds is vital to the management of water quality in the main stem rivers. Hence, policy makers should decide which places should be considered for restoration projects based on priority analyses. To carry out these evaluations in Korea, mathematical models are needed to forecast the environmental results after applying watershed restoration measures. However, the scope of sophisticated watershed modeling is very complicated, expensive and time consuming, and not really required for planning level decision making. Therefore, simpler evaluation methods should be applied, that can adequately discern for planning purposes the changes in aquatic environmental quality that can be expected in different watersheds after adapting restoration or protective measures. Thus, this research proposed to create a simple equation specifically for watershed planning. To create such a simple equation, three main tasks were undertaken. The tasks are as follows: (1) the creation of a selection program for available watershed models, (2) establish simple equations to be used instead of watershed models, and (3) verify the simple equations by comparing them with a physically based model (HSPF). In regards to the first task mentioned above, this dissertation presents a review of thirty three watershed models available for watershed planning and shows that these watershed models can not easily be applied to large-scale planning projects that are being undertaken by South Korea like the Four River Restoration Project. One of the main reasons for their inapplicability is that they require vast amounts of data and significant application effort to be used in a prioritization project involving many watersheds (Roesner, personal commucation). In addition, it is vital to select an appropriate watershed model that are realistically models a watershed's conditions and more specifically, to match users' needs. However a selection program has not yet developed, as well. Therefore, eight factors were selected for task 1 to examine the specific characteristics of each of the 33 watershed models in great detail. Based on the results of the 8 factors proposed, the selection program was developed to screen which will be most useful to a project. Based on these literature reviews of the 33 available watershed models but unrealistically complex models, it was determined that a simpler model utilizing accessible base data, such as land use type, is needed to evaluate and prioritize watersheds in the feasibility stage of a spatially large projectstudies for national based projects (i.e. National level). A correlation study between land use types and water quality parameters has been published (Tu, 2011, Mehaffey et al., 2005, Schoonover et al., 2005, etc.), however, the research examined the correlation between land usage and water quality in great detail, but did not address any correlations to implement real-based watersheds. Therefore, Task 2 is the development of simple equstions, for this task, two important sub-tasks were undertaken 1) Hydrology (rainfall), geology (slope), and land usage data were analyzed to verify their relationships with the water quality (BOD, COD, T-N, T-P) in the watershed, and 2) Simple Equations were constructed based on Statistical Methods (Excel Solver, Statistical Analysis Systems) and Data Mining (Model Tree, Artificial Neural Network, and Radial Based Function) in order to prove their accuracy. Thus, if the equations are accurate, they can be used to prioritize basins within a watershed with respect to their impact on water quality in the mainstem river. For the final task, task 3, Simple Equations were verified by comparing them with a physically based model, HSPF, based upon the real-based watersheds which are located in South Korea in order to prove the Simple Equations are capable of being a reliable alternative to physically based models. These simple equations could be used to allow management to identify and prioritize restoration and rehabilitation areas in a watershed even though sufficient data had yet been collected to satisfy the requirements of a physically based model.
Keywords: selection program; watershed models; simple equations